2021
DOI: 10.1002/agg2.20145
|View full text |Cite
|
Sign up to set email alerts
|

Coal char effects on soil chemical properties and maize yields in semi‐arid region

Abstract: Soil amendments with high carbon (C) content can be effective in semi‐arid regions where soils are characterized by low C. A field study was conducted in 2016–2018 to evaluate the effect of char on soil chemical properties and irrigated maize (Zea mays L.) yields in sandy loam fertilized with urea or composted manure. Carbon‐rich char used was a product of coal combustion residue from a local factory in western Nebraska. The experiment was arranged in a split‐plot randomized complete block design in four repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…(2020) and Panday et al. (2021) did not observe any yield benefits in a maize–dry bean–maize rotation when CCR was applied to soils with a C content of 10.1–15.0 g C kg −1 . In contrast, Maharjan et al.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…(2020) and Panday et al. (2021) did not observe any yield benefits in a maize–dry bean–maize rotation when CCR was applied to soils with a C content of 10.1–15.0 g C kg −1 . In contrast, Maharjan et al.…”
Section: Introductionmentioning
confidence: 91%
“…(2021) reported improved maize yield in a dry bean–maize–sugar beet rotation with CCR applied at >6.5 Mg C ha −1 on exposed sub‐soil with C of 7 g C kg −1 , indicating that CCR amendments might have more pronounced benefits in soils with lower C content compared to those with higher C content. This underlines the significance of soil type in influencing the effects of CCR on crop yield, with low C‐content soils potentially benefiting from CCR due to enhanced soil water retention and nutrient availability (Blanco‐Canqui et al., 2020; Panday et al., 2021). Additionally, factors such as crop rotations and crop phases could play a role in influencing crop responses to CCR, warranting further investigation.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The relatively high C content among different types of coal combustion residues makes this char also valuable for efforts to restore soil C storage in degraded soils (Blanco-Canqui et al, 2020). However, to the best of our knowledge, data on this char material to improve agricultural soil are limited to four published studies (Blanco-Canqui et al, 2020;Panday, Mikha, Collins, et al, 2020;Panday et al, 2021). From a 30-d column experiment Panday, Mikha, Collins, et al (2020) found that char applications did not affect leaching of NO 3 or emission of N 2 O from a sandy textured soil receiving mineral fertilizer.…”
Section: Core Ideasmentioning
confidence: 99%